2002
DOI: 10.1163/156853802760061778
|View full text |Cite
|
Sign up to set email alerts
|

Female activity patterns and aggressiveness in the strawberry poison frog Dendrobates pumilio (Anura: Dendrobatidae)

Abstract: Female strawberry poison frogs (Dendrobates pumilio) exhibit highly evolved maternal care, including tadpole transport and tadpole provisioning with unfertilized eggs. We observed that tadpole-rearing and mating activity are mutually exclusive behavioura l states in a Costa Rican population. Tadpole-rearin g females did not engage in courtship activity. Only non-rearing females courted. Non-rearing females occupied larger home ranges than tadpole-rearing females, which may be related to female selection of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Donnelly (1989a,b) provides convincing evidence that tadpole-rearing sites are a limited resource in the strawberry poison frog Dendrobates pumilio. These results have been confirmed through research on another D. pumilio population in which it was shown that the distribution of suitable tadpole-rearing sites influences the distribution of males and females in this species (Prö hl, 2002;Prö hl and Berke, 2001). Nevertheless, it has never been confirmed that males defend tadpole-rearing sites by agonistic interactions against intruders in their territories.…”
Section: Territoriality In Poison Frogsmentioning
confidence: 90%
See 2 more Smart Citations
“…Donnelly (1989a,b) provides convincing evidence that tadpole-rearing sites are a limited resource in the strawberry poison frog Dendrobates pumilio. These results have been confirmed through research on another D. pumilio population in which it was shown that the distribution of suitable tadpole-rearing sites influences the distribution of males and females in this species (Prö hl, 2002;Prö hl and Berke, 2001). Nevertheless, it has never been confirmed that males defend tadpole-rearing sites by agonistic interactions against intruders in their territories.…”
Section: Territoriality In Poison Frogsmentioning
confidence: 90%
“…Intrasexual aggressiveness in female D. pumilio has not been reported from other populations (McVey et al, 1981;Bunnell, 1973;Donnelly, 1989a;Prö hl and Hö dl, 1999). It might be peculiar to the population studied by Haase and Prö hl (2002) in which tadpole-rearing sites are inordinately abundant, and as a consequence female density was unusually high (6 10 females per 100 m 2 , A. Haase pers. comm.).…”
Section: Suggestions For Future Workmentioning
confidence: 90%
See 1 more Smart Citation
“…D. pumilio males and, to a lesser extent females, are intrasexually competitive (Pröhl & Berke, 2001;Haase & Pröhl, 2002). Pröhl & Berke (2001) reported that females choose their breeding territories based on the presence of tadpole rearing sites, whereas males choose their territories based on the presence of females.…”
Section: Introductionmentioning
confidence: 99%
“…Like in mammals, female O. pumilio heavily invest in maternal care mainly consisting of tadpole provisioning with nutritive eggs whose production requires high amounts of energy. There is another aspect in which female frogs behave like female mammals during pregnancy and lactation (Rosvall, ): females of the strawberry poison frog are more aggressive towards other females during periods of tadpole feeding (Haase & Pröhl, ).…”
Section: Discussionmentioning
confidence: 99%